The dollmaker - Allan, Nina (Other Press, 2019)
"Stitch by perfect stitch, Andrew Garvie makes exquisite dolls in the finest antique style. Like him, they are diminutive, but graceful, unique and with surprising depths. Perhaps that's why he answers the enigmatic personal ad in his collector's magazine. Letter by letter, Bramber Winters reveals more of her strange, sheltered life in an institution on Bodmin Moor, and the terrible events that put her there as a child. Andrew knows what it is to be trapped; and as they knit closer together, he weaves a curious plan to rescue her. On his journey through the old towns of England he reads the fairytales of Ewa Chaplin--potent, eldritch stories which, like her lifelike dolls, pluck at the edges of reality and thread their way into his mind. When Andrew and Bramber meet at last, they will have a choice--to remain alone with their painful pasts or break free and, unlike their dolls, come to life"--